2014
DOI: 10.1002/biof.1157
|View full text |Cite
|
Sign up to set email alerts
|

HMG‐CoA reductase inhibitors (statins), inflammation, and endothelial progenitor cells—New mechanistic insights of atherosclerosis

Abstract: Statins have been shown to favorably affect the prognosis of patients with risk factors to atherosclerosis-both as a primary and a secondary prevention. The beneficial effects observed with statin therapy are not merely related to changes in lipid profile but also are due to a positive effect on vascular inflammation and on immune-modulation of T lymphocytes and endothelial progenitor stem cells (EPCs). This dual effect has been demonstrated mainly in clinical trials where a change in endothelial function was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 109 publications
1
13
0
3
Order By: Relevance
“…It has been reported that sleep deprivation is associated with cardiac autonomic disorder, inflammation, and oxidative stress . Statin was reported to ameliorate inflammation in previous studies . In our study, we found that hsCRP levels were significantly lower in the statin group, thus it is possible that statin reduces inflammation and improves the LF/HF ratio.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been reported that sleep deprivation is associated with cardiac autonomic disorder, inflammation, and oxidative stress . Statin was reported to ameliorate inflammation in previous studies . In our study, we found that hsCRP levels were significantly lower in the statin group, thus it is possible that statin reduces inflammation and improves the LF/HF ratio.…”
Section: Discussionsupporting
confidence: 60%
“…[2][3][4] Statin was reported to ameliorate inflammation in previous studies. 27,28 In our study, we found that hsCRP levels were significantly lower in the statin group, thus it is possible that statin reduces inflammation and improves the LF/HF ratio. Statin can ameliorate oxidative stress.…”
Section: Potential Mechanismsmentioning
confidence: 49%
“…The anti-inflammatory effect of simvastatin was previously reported in different animal models [48,49] and clinical trials [50,51] . Generally speaking, HMG-CoA reductase inhibition was reported in earlier studies to have anti-inflammatory effects [52,53] . The anti-inflammatory effect of simvastatin may also be attributed to its ability to suppress inducible nitric oxide synthase expression [54] .…”
Section: Discussionmentioning
confidence: 99%
“…This can be especially debilitating in an older population prone to frailty and diminished HRQL. Reports of statin-induced cognitive changes are offset by inconsistent data, with some reports suggesting benefit attributable to reduced inflammation and improved vascular function (48,49). Again, few trials include older adults with intermediate and poor health, indicating a need for further study.…”
Section: Lipid Loweringmentioning
confidence: 99%